Macroeconomic Variables and Carbon Dioxide Emissions Nexus in Kenya - Onyango, J.; Kiano, E.; Saina, E. (Africa Environmental Review Journal, 2020)
Ever since the times of industrial revolution, the world is racing to attain high economic development at the expense of natural resources utilization. The pursuit has led to a raise in the exploitation of non-renewable resources through various human activities leading to emissions of greenhouse gases especially carbon dioxide (CO2) that causes global warming and eventually climate change with negative economic repercussions. This study sought to establish the macroeconomic variables and carbon dioxide emissions nexus in Kenya. The study further sought to establish the validity of Environmental Kuznets Curve for Kenya. The analysis is based on auto-regressive distributed lag model of spanning data over time series 1963 to 2017. The results revealed that an increase in the use of energy and population size worsens carbon dioxide emissions while sustainable Agriculture and industrialization reduces the prevalence of carbon dioxide percentage in the atmosphere. The study confirmed an inverted U shape confirming the validity of EKC hypothesis. The model also revealed forty five percent speed of adjustment of the disturbances from the year before in CO2e to equilibrium in the current year. As a policy implication, the study highlights sustainable technologies like carbon arrest and storing, demeaning clean and renewable energy for domestic and industrial use, green initiatives in building and construction, sustainable agriculture focusing on productivity and engaging the public on environmental preservation and management inter alia as essential to reducing carbon release.